Immunoreactivity of dendritic cells in foveolar lesions in borderline leprosy - Botelho, Gabriel Izan Santos (2020)
Leprosy is an infectious and contagious disease, whose etiologic agent is the Mycobacterium leprae, mainly characterized by neural and dermatologic injures. The tuberculoid and lepromatous leprosy types are called polar and considered stable forms. Between them there is the borderline group that shows immunologic instability with variable clinical forms, and it presents a lesion with infiltred border and center of healthy skin, called foveolar lesion. This study aimed to analyze the immunoreactivity of dendritic cells in the apparently healthy skin inside the central region and the infiltred edge of the foveolar lesion in borderline leprosy. It is an analytical and transversal study. CD1a and FXIIIa markers were used to count the dendritic cells in skin samples. A predominance of CD1a and FXIIIa cells in the foveolar border lesion was observed as compared to the center area of the lesion. The prevalence of dendritic cells at the edge of the foveolar lesion can be justified by the pattern of inflammatory and immune response to M. leprae. The distribution of M. leprae may be concentrated in this region, promoting a greater antigenic exposure. The comparison between the center and the edge of the foveolar lesion has obtained a quantitative difference indicating a basic function of dendritic cells in response to M. leprae and, consequently, in the course of the disease.